Emergence of Novel Coronavirus and COVID-19: whether to stay or die out?. (3rd March 2020) - Biswas, Asim; Bhattacharjee, Uttaran; Chakrabarti, Alok Kumar; Tewari, Devendra Nath; Banu, Hasina; Dutta, Shanta
Abstract: The last century has witnessed several assaults from RNA viruses, resulting in millions of death throughout the world. The 21st century appears no longer an exception, with the trend continued with escalated fear of SARS coronavirus in 2002 and further concern of influenza H5N1 in 2003. A novel influenza virus created the first pandemic of the 21st century, the pandemic flu in 2009 preceded with the emergence of another deadly virus, MERS-CoV in 2012. A novel coronavirus "SARS-CoV-2" (and the disease COVID-19) emerged suddenly, causing a rapid outbreak with a moderate case fatality rate. This virus is continuing to cause health care providers grave concern due to the lack of any existing immunity in the human population, indicating their novelty and lack of previous exposure. The big question is whether this novel virus will be establishing itself in an endemic form or will it eventually die out? Endemic viruses during circulation may acquire mutations to infect naïve, as well as individual with pre-existing immunity. Continuous monitoring is strongly advisable, not only to the newly infected individuals, but also to those recovered individuals who were infected by SARS-CoV-2 as re-infection may lead to the selection of escape mutants and subsequent dissemination to the population.